(untitled) (New York, 2000)
Varicella-zoster virus is a common human pathogen that causes varicella (chickenpox), establishes latency in sensory nerve ganglia and can reactivate many years later as herpes zoster. VZV is the only human herpesvirus for which vaccines to prevent both primary and recurrent infection are approved and VZV vaccines have had significant public health benefits. These achievements and new directions that are unfolding are described in this review of VZV basic and clinical research
Keywords: Varicella-zoster virus.,Chickenpox,Shingles (Disease),Bệnh thuỷ đậu; Bệnh Zona